Pemberdayaan Home Industri melalui Strategi Desain Merek dan Pemasaran Online - Hasanudin, Hasanudin; Muyasar, Rizky (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2023)
Micro, Small and Medium Enterprises (MSMEs) are start-up businesses managed by individuals or groups of people using certain capital whose existence plays a very important role in the current Indonesian economy. In this service activity, the MSMEs that are used as partners are the owners of the Traditional Herbal Medicine MSME business, Kunyit Asem and other MSME business actors in Cikeas Village, Bogor Regency. There were 20 participants who took part in the training. The aim of this service is so that MSME business actors in the Bogor Regency area can increase knowledge, creativity and innovation related to online marketing and the use of brands on products, so that the MSME products offered will be better known to the general public, reaching consumers in remote areas and wider marketing areas. Which will ultimately increase sales turnover, so that the MSME business being run will develop and absorb more workers. The method used in this PkM activity is in the form of material presentation lectures, question and answer discussions, and evaluations (pre-test and post-test) carried out by lecturers who understand the field of marketing management, especially related to the use of brands and online marketing. The results of this research are that MSME business actors and people in the Bogor Regency area who want to start a business and already have a business are able to manage and run a good business by implementing marketing management strategies through the use of brands and online marketing so that MSME business actors can develop their business which in the end will absorb more workers and assist the government in reducing poverty. It is expected that activities like this can be continued with similar activities in the next period. Apart from MSME business actors and the general public, they can continue to increase their knowledge and skills by participating in other activities such as webinars, seminars, training and coaching related to digital online marketing strategies to stimulate motivation, creativity and innovation, which will also increase the abilities of the players. MSME business in Cikeas Udik, Bogor Regency to develop their business.